Key features of New Zealand business cycles - Kim, Kunhong; Buckle, R.A; Hall, V.B (School of Management Working Papers, 1992)
Within a modern business cycle framework, this paper utilises basic statistical techniques to reexamine stylised empirical facts associated with business cycles in New Zealand since the midl 960's. The approach is essentially a bivariate one, and uses Hodrick-Prescott methodology for trend computations. Point estimates and GMM standard errors are presented for the amplitude of each variable's deviations from trend, degree of contemporaneous cyclicality and phase shift. Many relationships change markedly over time and, at least with this methodology, it is not easy to establish many "regularities" with confidence. "Real variable regularity" in a broad sense is confirmed, but a number of our other stylised empirical facts and uncertainties are not consistent with outcomes usually associated with prominent theoretical business cycle models. In particular, domestic price fluctuations in New Zealand have been basically countercyclical, and the real net exports share of GDP does not seem to have moved countercyclically over the past decade. No systematic cyclical tendency has been discovered for fluctuations in government purchases, and the scale of changes affecting the monetary sector over the past decade continues to present difficulties for establishing "financial regularities".